(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
Many of the existing learning support systems do not lived up to their promises when used in a real classroom environment. They lack flexibility and cannot be adapted to the needs of the tutors and that of the students. MoLekol is a smart and innovative learning platform which provides a plethora of facilities. These include regular ones like the ability to have different types of users, creation of courses, upload of course materials, week planners, creation of online tests and enrolments. However, MoLekol brings some innovative features as well. Now, tutors are able to monitor the attendance of their students, monitor their progress in assignments, mark their assignments online, collapse or extend course sessions easily and they have more control over the management of their course materials. Students also have facilities to form teams online, to allocate tasks to team members, to monitor the progress of their assignments and to submit it online. They can also view their attendance and their tests and assignments marks anytime after the information have been updated by the tutor. Although the system includes a superadministrator, his roles and responsibilities have remained basically the same as in current e-learning systems. MoLekol is expected to become a reference amongst learning support systems